2020
DOI: 10.1111/pim.12714
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps and MPO in models of susceptibility and resistance against Entamoeba histolytica

Abstract: The main effector mechanisms of neutrophils are the release of neutrophil extracellular traps (NETs) and myeloperoxidase (MPO). In this work, we evaluated the role of NETs and the activity of MPO in the interactions of rodent neutrophils with amoebae and in amoebic liver abscess (ALA)‐resistant and ALA‐susceptible models. We showed with in vitro assays that mice produced greater amounts of NETs and MPO than did hamsters, and the elastase activity was high in both models. However, the inhibition of NETs and MPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Pathological examinations of patients who died of COVID-19 indicate that vascular impairment and neutrophil extracellular trap (NET) formation seem to play a crucial role in fatal cases, in addition or in combination with various other host factors such as age, gender, immune status and comorbidities (1,(4)(5)(6)(7). NETs are extracellular DNA fibers released by activated neutrophils during the innate immune response in animals and humans (8)(9)(10). They are described as an innate immune defense mechanism against bacteria, viruses, fungi and parasites (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological examinations of patients who died of COVID-19 indicate that vascular impairment and neutrophil extracellular trap (NET) formation seem to play a crucial role in fatal cases, in addition or in combination with various other host factors such as age, gender, immune status and comorbidities (1,(4)(5)(6)(7). NETs are extracellular DNA fibers released by activated neutrophils during the innate immune response in animals and humans (8)(9)(10). They are described as an innate immune defense mechanism against bacteria, viruses, fungi and parasites (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The golden Syrian hamster is described as one potential animal model for SARS-CoV-2 infections (41,42). Furthermore, a study with Entamoeba histolytica identified NET formation in hamsters (9). Therefore, we hypothesized that the hamster is an animal model to investigate the immunepathology of SARS-CoV-2 infections.…”
Section: Introductionmentioning
confidence: 99%
“…Díaz-Godínez ( 21 ) suggested that NADPH oxidase, which induces oxidative metabolism, was involved in the release of NETs. Later studies showed that calcium ionophores could induce the production of NETs; that is, the activity of PAD4 was also involved in the release of NETs ( 20 , 57 ). However, these factors are not the key to the production of NETs stimulated by amoebae.…”
Section: Phylum Sarcomastigophora Class Loboseamentioning
confidence: 99%
“…Although both mice and hamsters could be used for these experiments, differences in their NET and MPO levels were observed ( 20 ). In vitro experiments showed that mice produced more NETs and MPO than hamsters, whereas the elastase activity in both groups was very high.…”
Section: Phylum Sarcomastigophora Class Loboseamentioning
confidence: 99%
“…In two animal models of amoebic liver abscess, one with hamsters (susceptible) and another with Balb/c mice (resistant), it was found that inhibition of MPO with 4‐aminobenzoic acid hydrazide, resulted in mice with larger abscesses and fewer damaged amoebas 111 . In addition, in vitro experiments showed that mouse neutrophils produced greater amounts of NET and MPO than hamster neutrophils did, and inhibition of MPO promoted an increase in amoeba viability 112,113 . Histones, proteins also found on NET, show microbicidal activity and may similarly participate in amoeba killing.…”
Section: Innate Immune Responsesmentioning
confidence: 99%